2021
DOI: 10.3390/ani11113267
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of In Vivo and In Vitro Digestibility in Rabbits

Abstract: The apparent dry matter digestibility of diets for rabbits was measured in vivo (ADMDvv) and in vitro with the Ankom DaisyII Incubator. Four diets were tested: low fiber (LF), LF + 5% of pregerminated fenugreek seeds (PGFS) (LF5), LF + 10% PGFS (LF10), and high fiber (HF). For the ADMDvv, feces samples were collected from 56 White New-Zealand × Californian rabbits fed the 4 diets; animals were randomly allocated into 4 groups and housed in individual cages. For the in vitro trial, 3 methods were tested: fecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…Because of the fiber-dense diet consumed by the horses in this study, the variations observed in the fiber degradation models may be attributed to the microbial population of the inoculum, thus donor diets containing higher soluble carbohydrates or lower NDF and ADF may produce different statistical models. Furthermore, in vivo and in vitro digestibility trials do not produce identical results [3,6,8]; thus, caution is warranted when translating the present in vitro models to an in vivo setting. Future investigation is warranted to determine if the models produced in this study are applicable using microbial inoculum from horses consuming diets of differing nutrient composition while also determining their relevance in vivo.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Because of the fiber-dense diet consumed by the horses in this study, the variations observed in the fiber degradation models may be attributed to the microbial population of the inoculum, thus donor diets containing higher soluble carbohydrates or lower NDF and ADF may produce different statistical models. Furthermore, in vivo and in vitro digestibility trials do not produce identical results [3,6,8]; thus, caution is warranted when translating the present in vitro models to an in vivo setting. Future investigation is warranted to determine if the models produced in this study are applicable using microbial inoculum from horses consuming diets of differing nutrient composition while also determining their relevance in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…Previous research has established estimates of in vivo true digestibility for various nutrients (i.e., non-structural carbohydrates, crude protein, and neutral detergent fiber) within equine feedstuffs [2]. The application of in vitro methods within the Daisy II incubator (ANKOM Technology Corporation, Fairport, NY, USA) has been validated to estimate feedstuff digestibility in hindgut fermenters such as horses [3,4], donkeys [5], and rabbits [6] with a variety of applications for digestibility research [7]. Previous studies support using fresh feces as a microbial inoculum source to simulate hindgut digestion in the horse compared to in vivo trials [3,4,8].…”
Section: Introductionmentioning
confidence: 99%
“…For reasons related to their advantageous speed and cost, prediction models for in vivo digestibility using regression analysis are being widely investigated for economically important animals (cattle, poultry, pigs, and rabbits), companion animals, and humans [6,[40][41][42]. Prediction models for in vivo digestibility using regression analysis have not only identified nutrients in foods, including carbohydrates [24], CP [43], and phosphorus [44], but have also verified the potential feasibility of prediction models using regression analysis for energy [23] and the postprandial glycemic index [45].…”
Section: Discussionmentioning
confidence: 99%
“…La digestibilidad in vitro y la estimación del valor nutritivo de las materias primas utilizadas en este proyecto se muestran en la Tabla 7, y los resultados son comparables a los obtenidos in vivo (Tassone et al, 2021) Estimaciones realizadas a partir de ecuaciones de predicción (Villamide et al, 2009) para estimar el valor nutritivo de piensos compuestos de conejos.…”
Section: Ms Cenizas Ee Pb Pb-fdt Fdt Fnd Fad Ladunclassified